2010
DOI: 10.1111/j.1447-0349.2010.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to caregiving of frail, older persons predict depression

Abstract: Reactions to caregiving and depression affect a carer's ability to continue in their caring role. This paper examines the relationship between reactions to caregiving and depression in carers of frail, older people and is a cross-sectional study of carers of community-living people (≥70years), identified as frail, who completed a postal questionnaire. Reactions to caregiving were evaluated using the Caregiver Reaction Assessment. Anxiety and depression symptoms were measured using the Hospital Anxiety and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
(55 reference statements)
1
17
1
Order By: Relevance
“…This is consistent with previous studies such as Aggar et al. , who found that 67% of next of kin that care for frail older people reported good self‐esteem. We found that the positive aspect of caregiving self‐esteem significantly lowered the risk of showing signs of anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies such as Aggar et al. , who found that 67% of next of kin that care for frail older people reported good self‐esteem. We found that the positive aspect of caregiving self‐esteem significantly lowered the risk of showing signs of anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…Following screening and full-text review, nine eligible articles were identified [2230]. Five studies were advanced to data abstraction and risk of bias assessment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aim was to examine associations between CR sociodemographic, caregiver and relationship characteristics with caregiver morbidity singly and after controlling for clinical characteristics of the CRs.90 dyads consisting of community dwelling older adults with mild or greater levels of cognitive impairment(MMSE <27) and their informal CGs.Mean age; 79 ± 6Female gender; 54%Mean MMSE; 23.4 ± 3.6Married; 54.4%Mean age; 61 ± 14Female gender; 81%Spouse of CR; 44%Child/inlaw of CR; 45.6%Faes 2011 [29]NetherlandsRandomized controlled trialRCT of a multifactorial fall prevention program. Aim was to assess whether intervention (program) was more effective than usual geriatric care in preventing falls in frail communitydwelling older fallers, with and without cognitive impairment, and in alleviating subjective caregiver burden in subjects’ CGs.33 dyads consisting of community dwelling older adults who had fallen at least once in the last 6 months and who met at least 2 of the FFS criteria, and their informal caregivers.No sociodemographic characteristics (e.g., age) reported.All CRs able to walk at least 15 m independently with or without walking aid.All CRs had life expectancy >12 months.All CRs had MMSE >15.Mean age (intervention/control); 67.3 ± 13.1/64.3 ± 14.3Female gender (intervention/control); 50/67%Living with CR (intervention/control); 55/47%Baseline ZBI (intervention/control); 5.2/6.0Total caregiving hours per week (intervention/control); 8.0/10.5Kim 2008 [30]USACross-sectionalTele-survey-based study comparing caregiving burden and distress, among CGs of 4 types of CRs: cancer, diabetes, dementia, frail older adults.606 CGs across all 4 groups, including 135 caregivers (“frail elderly” group) of CRs whom their CG described as “frail due to age.”(“Frail elderly” group only)Mean age; 81.69 ± 9.77(“Frail elderly” group only)Mean age; 46.23 ± 14.99Female gender; 47.4%Relationship to CR;Spouse/partner; 0.7%Child/in-law; 50.4%Sibling/in-law; 1.5%Grandchild/in-law; 18.5%Friend/neighbor/nonrelative; 17.8%Other; 11.1%*This publication represents the index study for a series of five papers by a single set of investigators [2226]. An explanation of the relationship between these articles appears in the “Results” section of the manuscript…”
Section: Resultsmentioning
confidence: 99%
“…Among caregivers of the general older population, including people likely to have a diagnosis of AD, Aggar et al [23] identified disrupted daily routine, health problems, financial strain and a lack of family support as important causes of depression and anxiety. Furthermore, there is an association between depression in caregivers and reduced physical well-being, such as disrupted sleep patterns, increased incidence of cardiovascular and metabolic diseases, lowered immunity and early transition to frailty syndrome [17].…”
Section: Resultsmentioning
confidence: 99%